The Effectiveness of Breast Milk Management Posters on the ability of mothers to Give Expressed Breast Milk and Storage To Improve Exclusive Breast Feeding on Working Mother at Ketapang Village East Kotawaringin Regency - Rohmah, Miftakhur; Dilly Dessy Fauzyah; Retno Palupi Yonni Siwi (Journal of Global Research in Public Health, 2023)
The low ability of mothers to express and store breast milk causes unreached exclusive breastfeeding, which has an impact on the quality of next generation and on the national economy. The purpose of this study was to determine the Effectiveness of Breastfeeding Management Posters on the Ability of Mothers to Give Expressed Breast Milk and Its Storage to Increase the Success of Exclusive Breastfeeding for Working Mothers in Ketapang Village, East Kotawaringin Regency.The research design was a one group pre-post test design with a pre-experimental approach. Respondents were taken by purposive sampling technique that met the inclusion and exclusion criteria with a sample of 30 people. The independent variable is the mother’s ability to give expressed breast milk and its storage to increase the success of exclusive breastfeeding in working mothers and the dependent variable is the breast milk management poster. Data was analyzed by the Wilcoxon test.The results showed that prior to the distribution of breast milk management posters, it was known that the majority of respondents 20 (67%) were in the incapacitated category. After giving out milk management posters, it was found that almost all respondents 28 (93%) were in the capable category.The results of data analysis show that the significance level is 0.000 < α = 0.05 so that H0 is rejected and H1 is accepted, thus there is an Effectiveness of Breast Milk Management Poster on the Ability of Mothers to Give Expressed Breast Milk and Its Storage to Increase the Success of Exclusive Breastfeeding for Working Mothers in Ketapang Village, East Kotawaringin Regency.Based on the results of the study, it was concluded that posters on management of breast milk are effective in increasing the ability of mothers to express breast milk and store it to increase the success of exclusive breastfeeding in working mothers.